2023
DOI: 10.1126/sciadv.adg0773
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization and potential interactions of Endozoicomonas and chlamydiae in microbial aggregates of the coral Pocillopora acuta

Abstract: Corals are associated with a variety of bacteria, which occur in the surface mucus layer, gastrovascular cavity, skeleton, and tissues. Some tissue-associated bacteria form clusters, termed cell-associated microbial aggregates (CAMAs), which are poorly studied. Here, we provide a comprehensive characterization of CAMAs in the coral Pocillopora acuta . Combining imaging techniques, laser capture microdissection, and amplicon and metagenome sequencing, we show that (i) CAMAs are located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…7A). Together, these two bacterial taxa can act as an important energy source for their coral host (Maire et al, 2023). Given that coral bleaching disrupts the nutritional symbiosis between corals and their algal Symbiodiniaceae endosymbionts (Boilard et al, 2020), the high relative abundance of Simkaniaceae suggests microbiome acclimation to the environment of the inner zone of West Hagåtña Bay in A. pulchra .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7A). Together, these two bacterial taxa can act as an important energy source for their coral host (Maire et al, 2023). Given that coral bleaching disrupts the nutritional symbiosis between corals and their algal Symbiodiniaceae endosymbionts (Boilard et al, 2020), the high relative abundance of Simkaniaceae suggests microbiome acclimation to the environment of the inner zone of West Hagåtña Bay in A. pulchra .…”
Section: Discussionmentioning
confidence: 99%
“…Given that coral bleaching disrupts the nutritional symbiosis between corals and their algal Symbiodiniaceae endosymbionts (Boilard et al, 2020), the high relative abundance of Simkaniaceae suggests microbiome acclimation to the environment of the inner zone of West Hagåtña Bay in A. pulchra . While recent years have seen increasing research on the role of Endozoicomonaceae on coral holobiont function, the potential importance of Simkaniaceae for coral holobiont health has only been recognized recently (Maire et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…SCF049.01 (Table S12A) [7]. Because these Symbiodiniaceae cultures are themselves symbionts of cnidarians, we asked whether A. australiensis Cla049 infects in hospite Symbiodiniaceae (within cnidarians), or cnidarians themselves that are known to be chlamydial hosts [2,[41][42][43]. Analysis of a recent dataset of 12,009 cnidarian 16S rRNA gene metabarcoding samples from 186 studies [44] showed that only five samples (each from a different study) harbored ASVs at least 99% identical to the 16S rRNA sequence of A. australiensis Cla049 (Table S12B).…”
Section: In Hospite Symbiodiniaceae May Not Harbor Algichlamydia Aust...mentioning
confidence: 99%
“…In addition to Symbiodiniaceae, corals associate with a wide range of microbes, including bacteria, fungi and archaea (Blackall et al, 2015;Maire et al, , 2023. Microbes can adapt faster than the coral host due to their short generation times, and it has therefore been hypothesised that the manipulation of coral microbial symbionts to enhance coral climate resilience may represent a valuable approach for coral reef conservation (Doering, Maire, van Oppen, & Blackall, 2023;Peixoto et al, 2017;van Oppen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%